Neutrophil functional heterogeneity is a fixed phenotype and is associated with distinct gene expression profiles. Issue 6 (2nd August 2022) - Maskarinec, Stacey A.; McKelvy, Margaret; Boyle, Kimberly; Hotchkiss, Halie; Duarte, Madelaine E.; Addison, Bechtler; Amato, Nicholas; Khandelwal, Sanjay; Arepally, Gowthami M.; Lee, Grace M.
Abstract: Differences in the ability of neutrophils to perform relevant effector functions has been identified in a variety of disease states. Although neutrophil functional heterogeneity is increasingly recognized during disease, few studies have examined neutrophil functional heterogeneity during periods of health. In this study, we systematically characterize neutrophil functional heterogeneity in a cohort of healthy human subjects using a range of biologically relevant agonists including immune complexes, bacterial ligands, and pathogens. With repeated testing over several years, we show that neutrophil functional capability represents a fixed phenotype for each individual. This neutrophil phenotype is preserved across a range of agonists and extends to a variety of effector functions including degranulation, neutrophil extracellular trap release, reactive oxygen species generation, phagocytosis, and bacterial killing. Using well‐phenotyped healthy human subjects, we demonstrate that neutrophil functional heterogeneity is characterized by differences in neutrophil gene expression patterns. Altogether, our findings demonstrate that while neutrophil function is highly heterogeneous among healthy subjects, each individual's functional capability represents a fixed phenotype defined by a distinct neutrophil gene expression profile. These findings may be relevant during disease states where the ability to perform relevant neutrophil effector functions may impact disease course and/or clinical outcome. Graphical Abstract: Differences in neutrophil functional capacity represent a fixed phenotype and are defined by distinct neutrophil gene expression profiles.